Effects of Immersion Time and 5-Phenyl-1H-tetrazole on the Corrosion and Corrosion Mitigation of Cobalt Free Maraging Steel in 0.5 M Sulfuric Acid Pickling Solutions - El-Sayed M. Sherif; Asiful H. Seikh (Journal of Chemistry)
The effect of exposure time and 5-phenyl-1H-tetrazole on the corrosion and corrosion mitigation of cobalt free maraging steel in 0.5 M H2SO4 pickling solutions has been reported using electrochemical and spectroscopic investigations. Potentiodynamic polarization data showed that the increase of immersion time from 0 min to 120 min increases the corrosion rate and decreases the polarization resistance of the maraging steel. On the other hand, the addition of PHTA and the increase of its concentration decrease all the corrosion parameters of the steel at all exposure test periods. Electrochemical impedance spectroscopy measurements agreed with the obtained polarization data. Scanning electron spectroscopy and energy dispersive X-ray investigations confirmed that the inhibition of the steel corrosion is achieved via the adsorption of the PHTA molecules onto the steel precluding its surface from being dissolved.